Impact of the variety on the adsorption of anthocyanins and tannins on grape flesh cell walls. (9th December 2021) - Abi‐Habib, Elissa; Vernhet, Aude; Roi, Stéphanie; Carrillo, Stéphanie; Jørgensen, Bodil; Hansen, Jeanett; Doco, Thierry; Poncet‐Legrand, Céline
Abstract: BACKGROUND: During winemaking, after extraction from the skins, anthocyanins and tannins adsorb onto the pulp flesh cell walls. The present study aimed to quantify the amounts adsorbed and their impact on wine composition, the impact of variety and ethanol on adsorption, and whether the presence of anthocyanins plays a role and impacts tannin adsorption. RESULTS: Anthocyanin and tannin fractions obtained by mimicking winemaking conditions were mixed with fresh flesh cell walls of two varieties: Carignan and Grenache. Adsorption isotherms were measured. Adsorption of tannins was higher with Carignan than with Grenache and decreased when the ethanol content increased. In comparison, anthocyanins were adsorbed in small amounts, and their mixing with tannins had no impact on their adsorption. The differences were related to differences in pulp cell wall composition, particularly in terms of extensins and arabinans. CONCLUSION: Adsorption of tannins, which can reach 50% of the initial amount, depends on the pulp cell wall composition. This needs to be investigated further. © 2021 Society of Chemical Industry.